2011
DOI: 10.1111/j.1574-6976.2010.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid biosynthesis in actinomycetes

Abstract: All organisms that produce fatty acids do so via a repeated cycle of reactions. In mammals and other animals, these reactions are catalyzed by a type I fatty acid synthase (FAS), a large multifunctional protein to which the growing chain is covalently attached. In contrast, most bacteria (and plants) contain a type II system in which each reaction is catalyzed by a discrete protein. The pathway of fatty acid biosynthesis in Escherichia coli is well established and has provided a foundation for elucidating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
175
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(178 citation statements)
references
References 159 publications
(289 reference statements)
2
175
0
1
Order By: Relevance
“…S3E in the supplemental material). In E. coli, odd-numbered fatty acids arise though utilization of propionyl primers as alternative substrates to acetyl-CoA for FAS by FabH (23,27). The low-abundance d 7 -C 16:0 peak that is present only in perdeuterated C 10 -fed E. coli wild-type or TMY32 [fabH::catR(pET-FabY)] may arise through utilization of d 7 -butyryl-CoA produced by the ␤-oxidation cycle as a FAS primer by either FabH or FabY, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…S3E in the supplemental material). In E. coli, odd-numbered fatty acids arise though utilization of propionyl primers as alternative substrates to acetyl-CoA for FAS by FabH (23,27). The low-abundance d 7 -C 16:0 peak that is present only in perdeuterated C 10 -fed E. coli wild-type or TMY32 [fabH::catR(pET-FabY)] may arise through utilization of d 7 -butyryl-CoA produced by the ␤-oxidation cycle as a FAS primer by either FabH or FabY, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1 in C. obtusifolia. Under the molecular function category, binding (15,016,42.95%) represented the most abundant term, followed by catalytic activity (14,067, 40.24%) and transporter activity (2024, 4.98%). About 19,424 unigenes were annotated as "metabolic process" category, suggesting this study may allow for the identification of novel genes involved in the secondary metabolite synthesis pathways.…”
Section: 13)mentioning
confidence: 99%
“…This reaction is catalyzed by acetyl-CoA carboxylase (ACCase). The ACCase gene was cloned and characterized from bacteria, animals, and plants 15,16) showed that the over-expressed ACCase gene could increase the content of lipid. Therefore, it was suggested that the ACCase catalyzes a rate-limiting step of the lipid biosynthesis pathway.…”
Section: Lipid Biosynthetic Genesmentioning
confidence: 99%
“…In contrast, ACC has been the subject of greater research focus primarily due to its potential as an antibiotic drug target (Wright and Reynolds, 2007;Chan and Vogel, 2010;Parsons and Rock, 2011). ACC catalyses the carboxylation of various acyl CoA substrates, such as acetyl CoA, propionyl CoA and butyryl CoA (Arabolaza et al, 2010;Gago et al, 2011). The products of these reactions feed into the fatty acid synthesis and polyketide synthesis pathways, resulting in the production of mycolic acids and multimethyl-branched fatty acids present in the cell envelope (Takayama et al, 2005;Gago et al, 2011).…”
Section: Biotin Is An Enzyme Cofactormentioning
confidence: 99%
“…ACC catalyses the carboxylation of various acyl CoA substrates, such as acetyl CoA, propionyl CoA and butyryl CoA (Arabolaza et al, 2010;Gago et al, 2011). The products of these reactions feed into the fatty acid synthesis and polyketide synthesis pathways, resulting in the production of mycolic acids and multimethyl-branched fatty acids present in the cell envelope (Takayama et al, 2005;Gago et al, 2011). These pathways are especially important in Mycobacterium sp., as the cell envelope contains a complex lipid bi-layer composed primarily of mycolic acid.…”
Section: Biotin Is An Enzyme Cofactormentioning
confidence: 99%